Parâmetros da marcha em longevos acompanhados pelo projeto atenção multiprofissional ao longevo (AMPAL) - Rodrigues, Fernanda Regina (2017)
Introduction: The increase in the proportion of oldest-old (80 years or more) raises the discussion about incapacitating events in this age group. Among the several functional difficulties that the oldest-old faces are the changes of gait, being an important complaint the difficulty of walk. Little is known about which gait parameters are related to this difficulty. Objective: To study the possible relationship between gait parameters and subjective perception of difficulty or easiness of walk in oldest-old. Methodology: A cross-sectional, descriptive and analytical study involving non- bedridden oldest-old. The sample consisted of oldest-old participants of the Multi- professional Attention to Oldest-old Project. Participants who presented, at the time of the evaluation, obvious signs of lack of body balance and who needed support from another person to avoid falling were excluded. The Zeno Walkway mat was used to evaluate gait parameters. Three gait tests were carried out: 10 meters with normal walking (slow), 10 meters with fast walking and the sit and stand test. Results: Participated in the study 71 oldest-old with a mean age of 84.4±4.23 years, 48 women (68%), 68% had good or very-good self-perception of health. The subjective performance on 400 meters walk was considered difficult in 31 (44%), easy in 28 (39%) and very easy in 12 (17%). Participants who reported difficulty were older and more frequently female, with no statistical significance. Oldest-old reporting ease and very easy to walk also reported higher frequencies of good or very good health self-perception (p = 0.004). The gait parameters with significantly different means between the groups with subjective perception of difficulty or ease of walking were: walking time, cadence, percentage and time of foot support, step and stride length, step and stride time, balance and walking speed. We observed that the three tests presented similar results. When studying different cutoff points for the dentification of difficulty in walking in women, the speed of 75cm/s during the slow walk test showed a sensitivity of 70% and specificity of 72%. For the fast walk 98 cm/s had a sensitivity of 70% and specificity of 68%. Conclusion: We conclude that the slow walking test presented the best safety with the same performance as the others. The speed of 75 cm/s in the slow walk test and 98 cm/s in the fast gait test was the parameters with the best performance for the identification of oldest-old women with gait difficulty. A larger sample of male oldest- old would be important for identifying the cut-off points for this gender. We also noted that the Zeno-walkway mat is a safe and efficient tool for longevity gait assessment.